Efektivitas Kebijakan Vos Estis Lux Mundi Dalam Penanganan Kasus Pelecehan Anak Oleh Imam : Studi Komparatif Dua Kasus Pelecehan Di Lingkungan Gereja Katolik - Nukak, Basilio Bryan de Mang; Pati Weking, Simon Petrus; Meicen, Yohanes Jetlty (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2025)
This study aims to analyse the effectiveness of the Vos Estis Lux Mundi (VELM) policy in handling cases of sexual abuse of minors within the Catholic Church. The study employed a qualitative approach through a case study method, comparing two real-life incidents: one case that has not yet received formal follow-up from Church authorities, and one case that has been handled internally by the Diocese and is being processed at the Holy See level. Data were obtained through direct interviews with the victims' families, conducted online via instant messaging applications, and analysed concerning the principles of canon law and the Church's child protection policies. The results show significant differences in reporting channels, victim protection, and institutional responses between the two cases. Furthermore, it was found that the main challenges in implementing VELM lie in the lack of community education, social pressure on victims' families, and limited pastoral support in assisting the recovery process. This study emphasises the importance of consistent implementation of universal Church policies at the local level for the sake of justice, transparency, and holistic recovery for victims.